Mast Cell Promotes the Development of Intracranial Aneurysm Rupture. Issue 11 (November 2020) - Furukawa, Hajime; Wada, Kosuke; Tada, Yoshiteru; Kuwabara, Atsushi; Sato, Hiroki; Ai, Jinglu; Lawton, Michael T.; Hashimoto, Tomoki
Abstract : Background and Purpose: Inflammation has emerged as a key component of the pathophysiology of intracranial aneurysms. Mast cells have been detected in human intracranial aneurysm tissues, and their presence was associated with intramural microhemorrhage and wall degeneration. We hypothesized that mast cells play a critical role in the development of aneurysmal rupture, and that mast cells can be used as a therapeutic target for the prevention of aneurysm rupture. Methods: Intracranial aneurysms were induced in adult mice using a combination of induced systemic hypertension and a single injection of elastase into the cerebrospinal fluid. Aneurysm formation and rupture were assessed over 3 weeks. Roles of mast cells were assessed using a mast cell stabilizer (cromolyn), a mast cell activator (C48/80), and mice that are genetically lacking mature mast cells (Kit W-sh/W-sh mice). Results: Pharmacological stabilization of mast cells with cromolyn markedly decreased the rupture rate of aneurysms (80% versus 19%, n=10 versus n =16) without affecting the aneurysm formation. The activation of mast cells with C48/80 significantly increased the rupture rate of aneurysms (25% versus 100%, n=4 versus n=5) without affecting the overall rate of aneurysm formation. Furthermore, the genetic deficiency of mast cells significantly prevented aneurysm rupture (80% versus 25%, n=10 versus n=8, wild-type versus Kit W-sh/W-sh mice). Conclusions: These results suggest that mast cells play a key role in promoting aneurysm rupture but not formation. Stabilizers of mast cells may have a potential therapeutic value in preventing intracranial aneurysm rupture in patients. Abstract : Supplemental Digital Content is available in the text.